Maxillary osteolysis after tooth extraction in a patient with rheumatoid arthritis: a case report - Nakajima, Hiroshi; Ohashi, Mizuki; Shishido, Kotaro; Masuda, Chieko; Okada, Toshie; Sumimoto, Wakako; Misaki, Toru; Nakamiti, Yuka (Journal of Japanese Society of Dentistry for Medically Compromised Patient, 2008)
We describe our experienced with a case of maxillary osteolysis associated with osteomyelitis after extraction of the left upper canine in a 76-year-old woman who had had rheumatoid arthritis since 1992 and was receiving methotrexate (MTX) and prednisolone (PSL). The patient noticed mild pain of the left upper canine in August 2006, but ignored it until the toothache worsende. She then consulted a dentist on October 23, 2006. A diagnosis of apical periodontitis was made, and the left upper canine was extracted on the same day. She was treated with cefaclor at a dose of 1, 000mg/day. However, her symptoms worsened further, and the patient was referred to us on October 31. On initial examination, the left maxillary gingiva was swollen and showed several fistulae. A CT scan revealed osteolysis of the maxilla at the same site. The white cell count was 8.1×103/mL, the erythrocyte sedimentation rate was 41mm/30min and 86mm/60min, the CRP was 3.74mg/L, and the ALP was 238IU/L. On the same day, oral administration of faropenem (FRPM) was started at 600mg/day. On November 2, her treatment was switched to intravenous ceftriaxone sodium (CTRX) at 2g/day. After switching to CTRX, biopsy was performed for a suspected tumor. The diagnosis was osteomyelitis of the maxilla. MTX was withdrawn, and the acute symptoms resolved on November 21. Intravenous administration of CTRX (2g/day) was started immediately before surgery, and the infected part of the left side of the maxilla was removed with the patient under general anesthesia. MTX was restarted, and there has been no recurrence of maxillary osteomyelitis or osteolysis as of April 2008. In patients with rheumatoid arthritis, the possibility of serious infection must be taken into account at the time of dental or oral surgical procedures, including tooth extraction. Physicians should be aware of the need for prior treatment of dentigerous infection and for periodic dental care in patients who require simultaneous treatment with drugs that affect immunity and bone metabolism, such as MTX and PSL.